Exciting fixed point results in revised fuzzy cone metric spaces under a new control function with supportive applications - Ravichandran, Thangathamizh; Mubeen Tajudeen, M.; Akgul, Ali; Abdalla, Mohamed; Hassani, Murad Khan (Fixed point theory and algorithms for sciences and engineering, 2025)
In the context of revised fuzzy cone metric spaces (RFCMS). This research attempts to present an innovative concept of tripled fixed point (TFP) conclusions employing a control function. A continuous, one-to-one self-map having subsequential convergence (SC) in RFCMS functions as the control function. Apart from that, under adapted contractive-type circumstances, distinct TFP conclusions are generated through employing the triangular characteristic of RFCM. To reinforce the findings, two illustrative examples are provided. Lastly, the theoretical conclusions are validated by showing that the solutions for a class of Volterra integral equations (VIEs) exist and are unique.